MHD and Thermal Radiation Effects on Channel Flow of Nanofluid with Nanoparticles in Different Shapes - Vadithya, Meenakshi; Naikoti, Kishan; Macha, Madhu (Journal of Applied Nonlinear Dynamics, 2026)
The present article evaluates the combined effects of magneto hydrodynamic and thermal radiation on channel flow of nanofluid with different shapes of nanoscale particles. In this paper Hamilton and Crosser's model is used to analyse the flow behavior and thermal diffusivity of nanofluids by considering different shape factors. The suitable non-dimensional variables imposed upon the governing equations which are restraining the flow and then they are transformed into a set of non-linear ordinary differential equations. Those equations have been solved by using the numerical scheme called Runge-Kutta-Fehlberg 45. The analysis of divergence in velocity and temperature profiles, for different fluid controlling parameters have been presented graphically and detailed discussion made on the results. The temperature of the fluid is maximum for the lamina shaped particle followed by column, tetrahedron, hexahedron and sphere shaped particles. Furthermore, a comprehensive discussion of the impacts of relevant parameters i.e., local nusselt number and local skin friction coefficient are also highlighted in graphs form.